2011
DOI: 10.3892/or.2011.1180
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of lactosylceramide and overexpression of a PSC833-resistant P-glycoprotein in multidrug-resistant human sarcoma cells

Abstract: Abstract. The selection pressure for resistance to chemotherapy is accompanied by the enhanced expression of ABC proteins and increased cellular glycosphingolipid content. Thus, a possible connection between glycosphingolipid metabolism and ABC proteins in drug resistance has been suggested. In the present study, we established two human multidrug-resistant (MDR) cell lines derived from MESSA sarcoma cells by culturing with increasing concentrations of doxorubicin (DX5 cells) or doxorubicin together with cyclo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…PSC833 alone did not produce significant adverse effects, but it increased the likelihood of toxic effects when used with antitumor drugs. For example, a significant pharmacokinetic interaction was observed when PSC833 was administered in combination with DOX and TAX [ 40 , 41 ], thus requiring a reduction in the doses of the anticancer drugs. It was subsequently shown that second-generation P-gp inhibitors significantly decreased the excretion of various drugs, thereby increasing the incidence of significant adverse effects [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…PSC833 alone did not produce significant adverse effects, but it increased the likelihood of toxic effects when used with antitumor drugs. For example, a significant pharmacokinetic interaction was observed when PSC833 was administered in combination with DOX and TAX [ 40 , 41 ], thus requiring a reduction in the doses of the anticancer drugs. It was subsequently shown that second-generation P-gp inhibitors significantly decreased the excretion of various drugs, thereby increasing the incidence of significant adverse effects [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that selenium as essential trace element plays a key role in the field of immunity intervention and tumor prevention [5][6]. However, natural seleno-polysaccharide is scarce in plants, animals and micro-organisms.…”
Section: Introductionmentioning
confidence: 99%